Complete mitochondrial genome of the top hat blenny, Omobranchus fasciolatoceps Richardson (Blenniiformes: Blenniinae) in Southern China Coast. Issue 9 (2nd September 2022) - Zhang, Tao; Wu, Shiwei; Yang, Lei; Ping, Hongling; Lu, Bin; Liang, Jun; Yu, Xuejun; Sui, Yanming; Liu, Yimeng; Shi, Huilai
Abstract: The complete mitochondrial genome sequence of Omobranchus fasciolatoceps was firstly described in this article. The total length of mitogenome was 16, 569 bp. It contains 13 protein-coding genes, 22 tRNA genes, and two ribosomal RNA genes. The overall base composition of H-strand was 29.04% A, 27.14% C, 27.89% T, and 15.93% G, with an A＋T bias of 56.93%. The phylogenetic analysis results showed that the O. fasciolatoceps was most closely related to O. elegans .